A genetic and dermatoglyphic study on periodontitis. - (:unkn) unknown (My University, 1993)
Periodontal diseases encompass a wide range of disease manifestations and processes from the mildest inflammation of gingiva to the most advanced destructive periodontitis with loss of attachment, bone tissue and teeth. No entirely satisfactory identification and classification exist in periodontitis especially for high risk early onset periodontitis (EOP) cases, because of insufficient knowledge about the aetiological and host factors and their overlapping clinical and laboratory features. In this study, the dermatoglyphics, which is a genetic test method, suggesting the modes of inheritances of hereditary diseases, was performed on 36 EOP and 20 adult periodontitis (AP) patients and 20 periodontally healthy individuals. The diagnostic value of this genetic test method, which is the study of the quantitative and qualitative characteristics of patterns of ridged skin, and the role of heredity on periodontal diseases are discussed.